Fresh water and international economic law - Brown Weiss, Edith (O.U.P. OxfordGB, 2005)
Focuses on the implications of the use of water as an economic good, the implications of commodification of fresh water, and the bearing of economic law on water issues. Examines the application of other areas of law, such as human rights, and analyses the implications for the economic uses of water.